Weight stigma among young adults in Thailand: reliability, validation, and measurement invariance of the Thai-translated weight self stigma questionnaire and perceived weight stigma scale - Chirawat, Paratthakonkun; Kamolthip, Ruckwongpatr; Rattaprach, Rattana; Nadhiroh, Siti Rahayu; Wan, Ying Gan (MDPI AG, 2022)
The previous studies found that the Weight Self Stigma Questionnaire (WSSQ) and Perceived Weight Stigma Scale (PWSS) have shown well-established psychometric properties for measuring weight stigma with strong reliability and validity from different languages. However, there is a lack of an appropriate instrument in assessing weight stigma in Thai samples. This study aimed to examine the Thai WSSQ and PWSS among Thai university students. Both instruments were also assessed for their measurement invariance across gender and weight status subgroups. A cross-sectional study was conducted on 801 university students in Thailand between January 2022 and July 2022. All participants completed a demographic questionnaire and a Thai version of the WSSQ, PWSS, and Depression Anxiety Stress Scale-21 (DASS-21) via an online survey. Reliability, validity, measurement invariance, and correlational analyses were performed to investigate whether the Thai versions of the WSSQ and PWSS psychometric properties were acceptable. Both translated questionnaires demonstrated overall acceptable psychometric properties and revealed a two-dimensional structure for the WSSQ, and unidimensional structure for the PWSS. Measurement invariance was obtained across gender and weight status subgroups. Additionally, both translated WSSQ and PWSS were significantly correlated with DASS-21. The Thai-translated WSSQ and PWSS showed strong validity, reliability, and factorial invariance across different subgroups for measuring weight stigma among Thai university students.